Improving English Soft Skills Through Integrated Task-Based Learning Methods in Vocational High Schools - Arvina Sholawati; Atris Yuliarti Mulyani; Difa Pratama; Halimatussa'diyah (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2022)
This study aims to find out about improving English language skills through the Integrated Task Based Learning method for vocational students. Based on the research objectives, the method in this study uses qualitative research methods with a literature review approach. The stages of the research carried out were the collection of articles and journals, reduction and summary of articles, discussion, and conclusions. Sources of research data are articles and related journals that have the same topic. The results of the study indicate that the ability to speak English is very important to be learned and mastered by vocational students. Improving their ability to speak English can be done through the ITBL method because it is very useful to prepare them to enter the world of work.